ChemInform Abstract: Palladium‐Catalyzed C‐2 C—H Heteroarylation of Chiral Oxazolines: Diverse Synthesis of Chiral Oxazoline Ligands. Issue 18 (April 2016) - Xi, Tuo; Mei, Yuncai; Lu, Zhan
Abstract: A series of differently substituted chiral oxazolines is prepared through palladium‐catalyzed C—H functionalization.